Teacher professionalism is the basis of quality student preparatio - Нevko Igor Vasilievich (Journal of Education, Health and Sport, 2019)
The article states that the professionalism of the teacher is the basis of qualitative preparation of students. The potential of a specialist can be revealed in his basic professionally defined structures of personality, activity, communication. Formation of which will characterize one or another level of his professionalism. Incidentally, one of the important requirements for the professional training of a future specialist is the formation of communicative competence. Only a friendly relationship between the teacher and the students can form the need for learning. One of the important factors in creating a positive mood in the learning process is the role of the teacher’s personality.